1972
DOI: 10.1021/ic50114a021
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure of 10-phenoxarsine chloride, C12H8OAsCl

Abstract: The crystal and molecular structure of 10-phenoxarsine chloride, CisHgOAsCl, has been determined by single-crystal X-ray diffraction methods. The unit cell is monoclinic: a = 5.7596 (6) A, b ~14,641 (2) A,c -13.788 (1) A, ß = 109.80 (1)°, ámeasd = 1.71 (1) g cm-3, and Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1972
1972
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…1/2H20 , has been crystallised (in contrast to arsenious acid). The structure consists of a 3D arrangement of tetrahedral AsO(OH)3 groups and H20 molecules linked by hydrogen bonding [30,49] 2.255 (As-C1) [58] R2AsO(OH), there is again tetrahedral coordination about As(V), e.g. phenylarsonic acid [51] and the herbicide, dimethylarsinic (cacodylic) acid [30,51].…”
Section: As ( V) Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…1/2H20 , has been crystallised (in contrast to arsenious acid). The structure consists of a 3D arrangement of tetrahedral AsO(OH)3 groups and H20 molecules linked by hydrogen bonding [30,49] 2.255 (As-C1) [58] R2AsO(OH), there is again tetrahedral coordination about As(V), e.g. phenylarsonic acid [51] and the herbicide, dimethylarsinic (cacodylic) acid [30,51].…”
Section: As ( V) Compoundsmentioning
confidence: 99%
“…Subsequently the structure of the ortho acid [57] showed that there was indeed an As=O bond in this type of structure. The As(III) fungicide, 10-phenoxarsine chloride [58], is included as it is possibly the only biologically active organo As(III) compound which has been structurally characterised.…”
Section: As ( V) Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of the weighting scheme showed no apparent dependence on [Fol or sin 0. The maximum NOTE (100), (010) and (001) Center, using programs previously described (Stuckey et al, 1972).…”
Section: Determination and Refinement Of The Structurementioning
confidence: 99%
“…The final atomic parameters are given in Table 1.t The identification of the atoms and the configuration of the molecule are shown in the OR TEP (Johnson, 1965) is smaller than that of 164.6(2) ° found in 10-(3-methoxyphenyl)-5,10-dihydrophenarsazine. In other similar compounds, the values of the folding angles are: 154.1 (4) ° in 10-methyl-5,10-dihydrophenarsazine (de Meester, Chu, Jovanovic & Biehl, 1986), 156.3 ° in 10-chlorophenoxarsine (Stuckey, Cordes, Handy, Perry & Fair, 1972), 169.2 ° in 10-chloro-5,10-dihydrophenarsazine (Camerman & Trotter, 1965), and 178.5 ° in 10,10'-thiodiphenoxarsine (Grindstaff, Cordes, Fair, Perry & Handy, 1972). The m-tolyl substituent is in an axial position relative to the central ring as found in the compounds already mentioned.…”
mentioning
confidence: 99%